Vantage point the sixth estate and other discoveries - Teodoro, Luis V. 1941- (Quezon City University of the Philippines Press, 2014)
Collection of essays on the Philippine political, social and economic condition.
Cynics and colonials -- Teachers and taught -- Weapons of war -- Their way of life -- Knowing the enemy -- Fiddlers by the Pasig -- Destroyer of worlds.
Keywords: Philippines -- Politics and government -- 21st century; Philippines -- Social conditions -- 21st century; Philippines -- Economic conditions -- 21st century